Study of Open Defecation Free (ODF) Achievements in Passo Village, Sub District Teluk Ambon Baguala, Ambon City - Noya, Hendrawati; Mazaya, Gusti Ihda; Soedjono, Eddy Setiady (Universitas Muhammadiyah Surakarta, 2015)
Steady promotion on water, sanitation, and hygiene to achieve the target of Universal Access 2019 becomes a priority of Ambon local government. Various programs have been executed including the construction of public toilet and and communal waste water treatment plant (WWTP). Despite these efforts, open defecation is frequently practiced particularly in remote areas. Inquiries on the areas which can be classified as the most high-risk areas regarding with open defecation have been conducted which include Passo village in Teluk Ambon Bagualasub-district as one of these areas. It is presumed that 831 families (26.64%) in Passo Village are still practicing it. This study aimed to determine the social and technical aspects related to the practice of open defecation in Paso village. Data collections were conducted through observation, interview, and questionnaire. Based on the analysis, the social aspects that affect to performance of Open Defecation Free (ODF) was mainly due to the low capacity of local communities in building latrines, while their consciousness and attitude upon sanitation were poor. As for the technical aspects, water shortages became the primary factor for the absence of toilet, in addition to the limited area to construct it. Communal toilet turns out to be a resolution for this problem.